2014
DOI: 10.1021/jp507682k
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Oxygen Permeability and Phase Separation Morphology of the Multicomponent Silicone Hydrogels

Abstract: In this article, the multicomponent copolymers were prepared by the copolymerization of two hydrophobic silicon-containing monomers bis(trimethylsilyloxy) methylsilylpropyl glycerol methacrylate (SiMA) and tris(trimethylsiloxy)-3-methacryloxypropylsilane (TRIS) with three hydrophilic monomers 2-hydroxyethyl methacrylate, N-vinylpyrrolidone, and N,N-dimethyl acrylamide. The copolymers were hydrated to form transparent silicone hydrogels. The oxygen permeability coefficients (Dk) of hydrogels were measured, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 45 publications
1
46
0
1
Order By: Relevance
“…Ying et al proposed a multiphase‐transition mechanism to explain this abnormal response in which there is an interaction between the soft and hard segments and the responsiveness of one affects the responsiveness of the other . As discussed in our previous report, the silicone phases and hydrogel phases are generated and aggregated during the copolymerization of hydrophilic and hydrophobic monomers . The silicone phase is the hard segment and the hydrogel phase is the soft segment in our prepared hydrogels.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Ying et al proposed a multiphase‐transition mechanism to explain this abnormal response in which there is an interaction between the soft and hard segments and the responsiveness of one affects the responsiveness of the other . As discussed in our previous report, the silicone phases and hydrogel phases are generated and aggregated during the copolymerization of hydrophilic and hydrophobic monomers . The silicone phase is the hard segment and the hydrogel phase is the soft segment in our prepared hydrogels.…”
Section: Resultsmentioning
confidence: 60%
“…The silicone hydrogels were prepared using the following method . The photoinitiator D‐1173 and crosslinker EGDMA were combined in a flask.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…49 The results showed that the internal compositions were also not homogeneous, and the content of silicon element in bulk hydrogel is obviously less than that on the surface. The surface of silicone hydrogel became hydrophobic mainly due to the enrichment of silicon group.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…So the dark areas were hydrophobic SiMA phase and the size of this phase region was about 100 nm, which was consistent with the result observed using TEM. 49 These phase separation structures made the surface of the hydrogel uneven, meanwhile, many tiny holes formed on the surface of SiMA hydrogel as shown in Figure 7A. Figure 2C showed the SEM image of the same SiMA hydrogel.…”
Section: Articlementioning
confidence: 97%